Farmer participatory research for cassava technology transfer in Asia: Constraints and opportunities - Howeler, Reinhardt H.; Henry, Guy (International Center for Tropical Agriculture, 1998)
Since 1994 a farmer participatory research (FPR) methodology has been used with the objective of enhancing the development and adoption of efficient cassava production practices that will reduce erosion, maintain soil productivity and increase the income of cassava farmers in Asia. This 5-year FPR project, funded by the Nippon Foundation in Japan and coordinated by CIAT, is being executed by national research and extension organizations in Thailand, Indonesia, China and Vietnam. Members of the FPR teams in each of these countries participated in a Workshop in July 1994 in Thailand to become familiar with the FPR philosophy and methodologies. Upon return, they conducted Rapid Rural Appraisals (RRA) in cassava growing regions in their country to select two suitable pilot sites for the project. In addition, they established demonstration plots to show the farmers of the pilot sites a range of management practices to control erosion and increase yield or income. During a field day farmers looked at and discussed the various options and selected 4-5 that were considered most useful for their own conditions in order to try these on their own farms. In 1995 the first FPR trials were set out by fanners on their own fields with help from FPR team members. In erosion control trials they established 2-5 treatments on a uniform slope and constructed sedimentation channels along the lower side of each plot to collect the eroded sediments and measure soil losses due to erosion. In addition, other technology components such as improved varieties, alternative intercrop systems and fertilizer treatments were offered and experimented with by farmers. At the end of the first year, farmers and FPR team members jointly harvested all the plots and calculated cassava and intercrop yields, as well as the amount of soil loss in each treatment. These results were discussed with the participating farmers in order to select the best treatments for the second year of testing in 1996. From the experiences obtained so far we have learned that farmers in the selected sites are interested in the trials, and are adapting and adopting several component technologies. However, the success rate has been varied, especially between different sites and countries. A number of limitations have been identified, both technical, financial, organizational and institutional. This paper assesses the results of the project and identifies and analyzes the various constraints that are currently limiting the project. In addition, new opportunities are proposed that may alleviate the constraints. The analysis is conducted within a framework of how to move the project from the pilot phase to an implementation phase in order to reach a wider audience and obtain greater adoption of the developed technologies.